Mathias Casimirus Sarbievijus’ Lechias: search for the sources and epical tradition - Ulčinaitė, Eugenija (Literatūra, 2015)
Three sources of imitation can be distinctly traced in Sarbievijus’ poem Lechias. One of the sources can be ascribed to the tradition of the epic poetry, especially, to the author’s adherence to Vergil’s Aeneid. The second source of imitation can be noted in the influence produced by the poetry of the Renaissance, when the loci communes, qualifying the antique poetry, used to be replenished by the attributes typifying the new times. The third and final influence was produced by the poetics and aesthetics of the Baroque, when the forms of verbal expression, filled with unexpected transformations, paradoxes and antitheses, held sway. Though Sarbievijus entered the history of literature first of all as a creator of the lyric poetry in Latin, his Lechias, though, testifies to the fact that he had also mastered the rules of the epic art, and that he had cherished the ambitions to create a heroic epic poem based on the history of Poland. The extant fragment of Sarbievijus’ poem Lechias sheds light on the development of the tradition of the antique epic poetry in Europe as well as on the influences and changes that tradition had undergone. Those influences and changes, on the other hand, had affected the movement of the poetic expression of the genres of the literature of the Baroque in Europe as well.